(3x+6)+(-4x+9)=

Simple and best practice solution for (3x+6)+(-4x+9)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3x+6)+(-4x+9)= equation:


Simplifying
(3x + 6) + (-4x + 9) = 0

Reorder the terms:
(6 + 3x) + (-4x + 9) = 0

Remove parenthesis around (6 + 3x)
6 + 3x + (-4x + 9) = 0

Reorder the terms:
6 + 3x + (9 + -4x) = 0

Remove parenthesis around (9 + -4x)
6 + 3x + 9 + -4x = 0

Reorder the terms:
6 + 9 + 3x + -4x = 0

Combine like terms: 6 + 9 = 15
15 + 3x + -4x = 0

Combine like terms: 3x + -4x = -1x
15 + -1x = 0

Solving
15 + -1x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-15' to each side of the equation.
15 + -15 + -1x = 0 + -15

Combine like terms: 15 + -15 = 0
0 + -1x = 0 + -15
-1x = 0 + -15

Combine like terms: 0 + -15 = -15
-1x = -15

Divide each side by '-1'.
x = 15

Simplifying
x = 15

See similar equations:

| -5x-2(-3x+6)=22 | | 24=4k-4 | | (1+x)+(x+4)=0 | | -8x-8x=-16 | | -6(5n-2)-10(7n-6)= | | 33=8u+1 | | x^2+25=2x+9 | | 2n^2-n+2=5 | | -6x=-9-3y | | -30=-3y | | 2-6x=0 | | x-5(x-6)=2 | | 6r-(r+2)=23 | | 10t^3-40t=0 | | -4x+3=10x-1 | | 6r-(r+2)=22 | | p+16=27 | | x^2+y^2-2x-5.4y+7.29=0 | | (X+1)+(x+4)= | | -7=8x+5-4x | | -15+x=-14 | | 30+y=33 | | x=sqrt(x+13)+7 | | -2(-2b+5)+8b=14 | | 3(x-5)+4x= | | 2d+5=30-3d | | 1/7+26=4/7-4 | | 1_7+26=4_7-4 | | (a^2-4b)(a^2+2ab+b^2)= | | 14y-4=9y+11 | | 3(2g-15)+9g=14 | | 3a^2-5a-9=-3 |

Equations solver categories